2011
DOI: 10.1021/jp209746n
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Study of Molecular Motion of Benzene and n-Decane Confined in the Nanocavities of Metal–Organic Frameworks

Abstract: The molecular motion of benzene and n-decane confined in the nanocavities of [Zn4O(O2CC6H4CO2)3] n (IRMOF-1) was investigated in terms of the temperature dependence of the proton spin–lattice relaxation time (1H T 1). Both substances exhibited two components of T 1, below 216 K for benzene and 181 K for n-decane, indicating that the guest molecules are localized separately in large and small cavities. For n-decane below 181 K, methyl reorientation is excited although the rate of reorientation in large and sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Although the confined molecules may not always form ordered structure in a micropore, micropores can be organized in an ordered pattern utilizing the periodicity of a crystal. This establishes long-range regular arrangement of the molecules under confinement and collaborative molecular assembly in microporous matrix systems (Ueda et al, 2012). Such a candidate of porous system with well-defined pore structure and high crystallinity is isoreticular metal-organic frameworks (IRMOFs), a series of porous compounds with regular and homogeneous pores (Eddaoudi et al, 2001).…”
Section: Gupta and Bhattacharyya 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the confined molecules may not always form ordered structure in a micropore, micropores can be organized in an ordered pattern utilizing the periodicity of a crystal. This establishes long-range regular arrangement of the molecules under confinement and collaborative molecular assembly in microporous matrix systems (Ueda et al, 2012). Such a candidate of porous system with well-defined pore structure and high crystallinity is isoreticular metal-organic frameworks (IRMOFs), a series of porous compounds with regular and homogeneous pores (Eddaoudi et al, 2001).…”
Section: Gupta and Bhattacharyya 2012mentioning
confidence: 99%
“…Such a candidate of porous system with well-defined pore structure and high crystallinity is isoreticular metal-organic frameworks (IRMOFs), a series of porous compounds with regular and homogeneous pores (Eddaoudi et al, 2001). Among the IRMOFs, [Zn 4 O(BDC) 3 ]n (BDC = benzene-1,4-dicarboxylate) (IRMOF-1) is the prototype of a series of these compounds where zinc oxide and terephthalic acid moieties are three-dimensionally connected with each other establishing a porous framework resembling "a jungle gym" (Ueda et al, 2012).…”
Section: Gupta and Bhattacharyya 2012mentioning
confidence: 99%
“…Ueda et al 329 studied the motion of benzene and n-decane as guests within micropores of a metalorganic framework (MOF) system. They measured temperature dependence of 1 H T 1 and were able to characterize the molecular dynamics of both guests.…”
Section: Synthetic Polymers In Solutionmentioning
confidence: 99%
“…Recently, from our own focus on the properties of guest molecules confined in IRMOF-1, we found that several guest molecules adsorbed in IRMOF-1 exhibit thermal anomalies contracting with the melt and/or solid-solid phase transitions, and it was also discovered that these correspond to the phase transition derived from the guest molecules. [24][25][26] In the case where benzene is the guest, two thermal anomalies were observed at 216 K and 150 K. 25,26 Both of these peaks were detected at lower temperatures than the melting point of liquid benzene at 279 K, implying that the solid-solid transition takes place in benzene within the IRMOF-1 framework; this transition is not observed in the bulk phase. Our previous study revealed the dynamical structures of the guest molecules at various temperatures using solid-state 1 H NMR, and elucidated the correlation between the phase transition and the dynamic behaviour of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed the dynamical structures of the guest molecules at various temperatures using solid-state 1 H NMR, and elucidated the correlation between the phase transition and the dynamic behaviour of benzene. 26 Based on the temperature dependence of 1 H T 1 , the local structure and the dynamic behaviour of benzene in IRMOF-1 could be clarified. Occurrence of the solid-solid phase transition at 150 K leads to acceleration of the isotropic reorientation, accompanying intra-cavity migration of benzene in the small cavities, but there is no modulation of the molecular motion of benzene in the large cavities.…”
Section: Introductionmentioning
confidence: 99%